Investigating the Self-Efficacy and Professional Burnout level among Government Schools English Foreign Language Teachers in Lahore - Hina Sarwat1,; Dr. Aamir Hayat2,; Afshan Kanwal3,; Dr. Madieha Akram4,; Ezza Jabbar5, (Al-Qanṭara, 2024)
The core objective of this research study was to delve into the intricate relationship between self-efficacy and professional burnout within the educational sector, especially focusing on teachers instructing English as a non-native language, who may be grappling with heightened stress levels. A mixed-methods approach was used for the present research, targeting English teachers across various educational levels in Lahore. The study encompassed a sample size of 316 participants, carefully selected from a total population of 1415 English teachers in Lahore, utilizing a simple random sampling technique. Meticulously designed and well-structured questionnaires were distributed and collected from respondents through a Google link. Subsequently, the collected data underwent thorough analysis using (SPSS). The comprehensive analysis of this research underscores a discernible relationship between self-efficacy and professional burnout among English teachers in public schools in Lahore. The core assumption posits that a diminished level of self-efficacy corresponds to an elevated level of burnout among the selected English teachers. The findings highlighted the existence and persistence of this issue among a subset of English teachers. Key Words: Self efficacy, Professional Burnout, English language ,Teachers, Lahore District